Periodicity and input data grouping procedures in a climatological water balance - Souza, Jorge Luiz Moretti de; Gurski, Bruno Cesar; Adamuchio, Jessé; Jerszurki, Daniela (Scientia Agraria, 2018)
We aimed to evaluate the influence of periodicity of input data on values of output components of a climatological water balance (WB) in Goiânia and Ponta Grossa, Brazil, considering different shifts in total available water in soil and two input data grouping procedures. It was considered a two years-data series of climate variables provided by a near automatic meteorological station and readily available water (RAW) ranging from 10 to 160 mm, with an interval of 15 mm. WB output components were evaluated considering different entry data procedures for precipitation (P) and reference evapotranspiration (ETo): WBgd – WB with daily P and ETo, with output components grouped into periods; and WBP - P and ETo grouped into periods, and later used in WB estimations. The periodicity and input data grouping method may show a great effect in WB estimations. For activities that require greater detail and accuracy, it is recommended to perform as WBgd instead WBP. Estimated errors tend to increase from short to long periodicities and for lower soil water availability. The soil water storage had the highest daily average deviations, showing great increase for short periodicities and higher readily available water values.